A novel de novo COL1A1 mutation in a Thai boy with osteogenesis imperfecta born to consanguineous parents - Tongkobpetch,Siraprapa (2017)
Abstract Osteogenesis imperfecta (OI) is genetically heterogeneous. Mutations in COL1A1 and COL1A2 are responsible for at least 90% of the cases, which are transmitted in an autosomal dominant manner or are de novo events. We identified a Thai boy with OI whose parents were first cousins. Because the proband was the product of a consanguineous marriage, we hypothesized that he might be homozygous for a mutation in a known gene causing a recessive form of OI. Using whole exome sequencing (WES), we did not find any pathogenic mutations in any known gene responsible for an autosomal recessive form of OI. Instead, we identified a COL1A1 frameshift mutation, c.1290delG (p.Gly431Valfs*110) in heterozygosis. By Sanger sequencing, the mutation was confirmed in the proband, and not detected in his parents, indicating that it was a de novo mutation. These findings had implication for genetic counseling. In conclusion, we expanded the mutational spectrum of COL1A1 and provided another example of a de novo pathogenic mutation in heterozygosis in a patient born to consanguineous parents.